ISSUES OF IMPROVING THE TEACHING METHODOLOGY OF "ENGINEERING GRAPHICS" IN TECHNICAL HIGHER EDUCATION INSTITUTIONS ON THE BASIS OF AN INNOVATIVE APPROACH - Khakimova Malika (American Journals, 2024)
In the article, it is proposed to improve the teaching methodology of "Engineering graphics" in technical higher education institutions based on an innovative approach, by defining 3 levels of the context of the content of graphic sciences. Also, the control levels of the system for diagnosing the level of development of the components of professional competence of the future specialist are defined.
Keywords: Assignment, knowledge, drawing geometry, engineering graphics, construction drawings, homework, job option, construction drawing, computer graphics.